Beyond The Limit of A Theory Indonesian Case of Islamic Banking Accounting Standards - Hendi Yogi Prabowo (Jurnal Akuntansi dan Auditing Indonesia, 2003)
Indonesian Islamic banking is not just another banking maneuver from Bank Indonesia (BI) to grasp more customers than before, but it is a never ending source of innovations in economics thoughts in which accounting is undeniable part. Not before the establishment of PSAK No. 59 did Indonesian banking scholars and practitioners realize that currently adopted conventional accounting standards might have been enough for conventional banks, but they would never be enough for Islamic banks. Some flaws are too real to ignore in the conventional accounting theory that could cause improper information presentation in Islamic bank. Of ways to fix things that was done wrong previously, the best is to walk beyond the conventional accounting theory and find what accounting really is for an Islamic bank as it possesses some unique characteristics a con¬ventional bank does not.